Identifying the Characteristics of Job Analysis in TVET: A Combined Systematic Literature Review and Bibliometric Analysis - Muhamad Riyan Maulana; Putu Sudira; Priyanto Priyanto; Yanuar Agung Fadlullah; Arya Yusuf (FKIP - Universitas Riau, 2026)
This study aims to map the development of job analysis and job characteristics in the context of TVET from 2005 to 2025 using a bibliometric approach combined with a Systematic Literature Review (SLR). Data from Scopus were analyzed with VOSviewer to identify dominant keywords and visualize collaboration networks and bibliographic coupling at the document, source, author, organization, and country levels. The bibliometric results highlight that job analysis, work characteristics, and competency development are the primary research focuses, with trends shifting towards industry-based curriculum development, workplace assessment, and competency mapping driven by technological advancements. Influential journals such as the Journal of Vocational Rehabilitation, Journal of Occupational Rehabilitation, BMC Public Health, Work, and Brain Injury emerged as key sources. The United States was the leading contributor, followed by Germany, Switzerland, and other Western European countries, with Taiwan and South Korea showing growth in Asia. At the author level, Fong Chan, Gary R. Bond, and Clara E. Dismuke-Greer were central figures in the referential network. The SLR findings underscore the importance of job analysis in fostering continuous learning, assessment validity, teacher competency, and inclusive vocational pathways, with emerging trends and developments in job analysis research in TVET discussed.